Vplyv zadlženosti na rentabilitu poľnohospodárskych podnikov na Slovensku - Tomáš Rábek; Marián Tóth; Zuzana Strápeková; Ivan Holúbek (Trendy v podnikání, 2018)
The paper evaluates the development of bank loans in Slovak agriculture and analyses selected financial ratios of a set of agricultural farms. The data used for the analysis are from Central bank of Slovak republic and the database of Ministry of Agriculture and Rural Development of the Slovak Republic, over the period 2009 - 2016. Expansionary monetary policy leads to a decrease in interest rates, which was reflected in an increase in volume of bank loans in Slovak agriculture. Also, the number of failed loans has increased. Farmers generally have low return on equity. In the article we analyse the cost of debt and cost of equity to measure the potential effect of financial leverage, which can increase the return on equity of the farms.